2022
DOI: 10.3389/fendo.2022.826757
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Circulating PCSK9 Levels and Gestational Diabetes Mellitus in a Chinese Population

Abstract: BackgroundPrevious studies reported that proprotein convertase subtilisin/kexin type 9 (PCSK9) was a key player in the regulations of lipid metabolism and glucose homeostasis. The current study aimed to detect the expression of PCSK9 in pregnant women with gestational diabetes mellitus (GDM) and investigate the possible relationships between PCSK9 and related metabolic phenotypes in GDM.MethodsCirculating PCSK9 levels were determined by ELISA kit in a cohort of subjects with GDM (n = 170) and normal glucose to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the current study, it was found that triglyceride levels were higher in the survival group than in the death group, but the differences in cholesterol levels between the two groups were not significant, these results were consistent with previous studies [ 25 ]. Furthermore, though some studies reported positive correlations between circulating PCSK9 and lipid levels in healthy populations and cardiovascular patients [ 26 , 27 ], these relationships were not significant in septic patients. Lipid metabolism was complex under an inflammatory state, inflammatory factors play an important role in the regulation of lipid metabolism, and serum lipid levels are shared largely variations in patients with inflammatory disease [ 28 ].…”
Section: Discussionmentioning
confidence: 97%
“…In the current study, it was found that triglyceride levels were higher in the survival group than in the death group, but the differences in cholesterol levels between the two groups were not significant, these results were consistent with previous studies [ 25 ]. Furthermore, though some studies reported positive correlations between circulating PCSK9 and lipid levels in healthy populations and cardiovascular patients [ 26 , 27 ], these relationships were not significant in septic patients. Lipid metabolism was complex under an inflammatory state, inflammatory factors play an important role in the regulation of lipid metabolism, and serum lipid levels are shared largely variations in patients with inflammatory disease [ 28 ].…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence indicates that lipid metabolism correlates with gestational diabetes mellitus and preterm birth, both of which are common complications of pregnancy and pose serious risks to maternal-fetal health, making it imperative to find new and effective preventive measures for both conditions [2,3,40,41]. According to findings from epidemiological and clinical trials, elevated serum PCSK9 levels could lead to an increase in diabetes and gestational diabetes incidence, but the genetic results were not supportive [42,43]. The anti-inflammatory benefits of statins have shown potential in preclinical studies for treating preterm birth; however, these results are contradicted by the increased preterm birth rate with the use of statins in preeclampsia patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 [79], APCDD1 [80], SFRP4 [81], MFAP5 [82] and PKP2 [83] are associated to the risk of obesity. Studies show that PCSK9 [84] and SFRP4 [85] are involved in the process of gestational diabetes mellitus. The PCSK9 [86], SEMA3A [87], SFRP4 [81] and BMP6 [88] were found as potential biomarkers for diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%